Optimization of Quadruple Helix Using RUMEUNG App for Sustainable Tourism Development in West Java - Nur Hendrasto, Sutopo, Elang Ilik Martawijaya, Abdullah Haidar (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2024)
The development of tourism concepts requires collaborative efforts across multiple stakeholders. This study focuses on enhancing the tourism sector through the